Knockdown of Annexin A1 induces apoptosis, causing G2/M arrest and facilitating phagocytosis activity in human leukemia cell lines - Hasan Masyitah; Kumolosasi Endang; Jantan Ibrahim; Jasamai Malina; Nazarudin Norlaili (Acta Pharmaceutica)
Annexin A1 (ANXA1) is an endogenous protein involved in the control of proliferation, cell cycle, phagocytosis, and apoptosis in several types of cancer. To investigate the effects of ANXA1 knockdown in leukemia cells, transfection with specific ANXA1 siRNA was performed. Cell cycle and apoptosis were analyzed using flow cytometry and a mechanism involving caspases and Bcl-2 was quantified using Western blotting. Phagocytosis activity was evaluated using hematoxylin & eosin staining. The ANXA1 expression was significantly downregulated after the knockdown and apoptosis was induced in tested cells. The expression of caspase-9 and -3 increased in U937 and Jurkat cells respectively. Bcl-2 expression was downregulated in K562 and Jurkat cells while upregulated in U937. The number of leukemic cells arrested at the G2/M phase and the phagocytosis index were significantly increased in transfected cells. This suggests that ANXA1 knockdown might be a potential approach in the therapeutic strategy for leukemia.